Women's preferences for integrating multi-product pre-exposure prophylaxis delivery programs within services for sexually transmitted infections and reproductive health care in Uganda: a discrete choice experiment - Kamusiime, Brenda; Smith, Patricia M.; Nalumansi, Alisaati; Wood, Tara E.; Eram, George; Kasiita, Vicent; Ssendiwala, Paul; Nakyanzi, Agnes; Bambia, Felix; Muwonge, Timothy R.; Mujugira, Andrew; Montgomery, Elizabeth T.; et al. (Frontiers in Reproductive Health, 2025)
IntroductionHIV prevention is paramount for adolescent girls and young women (AGYW) in Uganda, and oral pre-exposure prophylaxis (PrEP) is not always a suitable option. With emerging novel HIV prevention products (e.g., ring, injectables), there are opportunities to explore AGYW preferences to inform strategies for integrating PrEP choice into routine care.MethodsFrom January–September 2024, we recruited AGYW aged 16–25 years from community sites in Kampala, Uganda for a cross-sectional discrete choice experiment (DCE) to determine the most preferred attributes and levels of multi-product PrEP programs. The DCE was developed via literature review, informal conversations with AGYW, and cognitive interviewing among AGYW using a prototype instrument. In the final iteration, attributes (and levels) included: method of PrEP information dissemination (WhatsApp, brochure, in-person consultations), PrEP counseling delivery (virtual, group, in-person counselling), proximity of PrEP location (nearer to or far from work/school/home), type of facility (private or government clinic, pharmacy), availability of additional services (STI testing and treatment, family planning, no additional services), client wait times (5, 30, 90 min), and associated costs (small, none). Participants responded 9 times to the question “Which PrEP program would encourage you to use PrEP?” and each time a different set of randomly-assigned choices of 2 scenarios were presented. Multinomial logit modeling was used to estimate preference weights and importance scores.ResultsOf 343 AGYW screened, 300 consented to participate (median age: 21 years, IQR: 20–23), with 38.3% having oral PrEP experience and 71.7% reporting recent condomless sex. “Access to other services” in conjunction with PrEP dispensing had the greatest influence on PrEP program choice (importance score: 27%) with preferences for STI testing and treatment (preference weight: 0.39, 95% CI: 0.32, 0.47) and family planning (PW: 0.14, 95% CI: 0.07, 0.21) greater than stand-alone PrEP programs. The type of facility offering PrEP (importance score: 9.7%), method used for PrEP information dissemination (importance score: 10.2%), and proximity of the PrEP location (importance score: 6.9%) were not very influential.DiscussionYoung women's preference for PrEP services to be offered in conjunction with STI and/or reproductive health services indicates an opportunity to integrate current and future PrEP delivery within these existing services.